Placenta Percreta Invading Broad Ligament and Parametrium in a Woman with Two Previous Cesarean Sections: A Case Report - Mansoureh Vahdat; Abolfazl Mehdizadeh; Elaheh Sariri; Shahla Chaichian; Zahra Najmi; Maryam Kadivar (Hindawi Limited, 2012)
Introduction. The incidence of placenta accreta has dramatically increased due to increasing caesarean section rate all over the world. Placenta percreta is the most severe form of placenta accretes. It frequently results in maternal morbidity and mortality mainly caused by massive obstetric hemorrhage or emergency hysterectomy. Percreta invading into the broad ligament has rarely been previously reported. Case presenting. We presented a case of placenta percreta invading left broad ligament and parametrium in a woman with two previous cesarean sections, which led to massive intraoperative hemorrhage during hysterectomy and transient ischemic encephalopathy. Conclusion. In cases of parametrial involvement, it would be more difficult to decide whether to remove placenta or leave it in site. In surgical removal neither local excision of placental bed and uterine repair nor traditional hysterectomy is adequate if parametrium invaded by placenta. We suggest delayed elective hysterectomy in such cases. So, pregnancy-induced pelvic congestion would be decreased, we can gather an expert team of gynecologists, urologists, and vascular surgeons, we could get plenty of blood products, and we may have the chance to administer methotrexate.